Investigating the Alignment Between the CELPIP-General Reading Test and the Canadian Language Benchmarks: A Content Validation Study - Chen, Michelle Y.; Flasko, Jennifer J. (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2020)
Seeking evidence to support content validity is essential to test validation. This is especially the case in contexts where test scores are interpreted in relation to external proficiency standards and where new test content is constantly being produced to meet test administration and security demands. In this paper, we describe a modified scale- anchoring approach to assessing the alignment between the Canadian English Language Proficiency Index Program (CELPIP) test and the Canadian Language Benchmarks (CLB), the proficiency framework to which the test scores are linked. We discuss how proficiency frameworks such as the CLB can be used to support the content validation of large-scale standardized tests through an evaluation of the alignment between the test content and the performance standards. By sharing both the positive implications and challenges of working with the CLB in high-stakes language test validation, we hope to help raise the profile of this national language framework among scholars and practitioners.